The Dynamics of Job Creation Law Implementation in Addressing Digital Disruption: Transformation and Harmonization of Business Law in Indonesia - Lily Maryam Nasution; Lia Hartika; Rika Githamala Ginting; Syahrial Arif Hutagalung; Dita Kartika Sari Hasibuan; Yessi Kurnia Anjani Manik (Ali Institute of Research and Publication, 2026)
The rapid advancement of digital technology has fundamentally transformed business legal systems, demanding more adaptive and responsive regulatory frameworks. In Indonesia, the Job Creation Law was enacted through an omnibus law approach to simplify regulations and support the digital economy; however, its implementation continues to face significant challenges, including regulatory disharmony, normative gaps, and legal uncertainty. This study analyzes the dynamics of the Job Creation Law's implementation in responding to digital disruption in Indonesia's business law sector, along with the challenges encountered and the government's role in regulatory harmonization. Using a normative legal method with a descriptive-analytical approach, this study employs statutory and case-based approaches, drawing on secondary data analyzed qualitatively. The findings indicate that while the Job Creation Law has successfully shifted business law toward a more adaptive, risk-based regulatory paradigm, its implementation remains constrained by cross-sectoral regulatory fragmentation, jurisdictional limitations in the borderless digital economy, and insufficient institutional capacity and digital legal infrastructure. The harmonization of business law in the digital era ultimately depends on policy consistency, inter-agency synergy, and a sustained balance between fostering innovation and ensuring adequate legal protection for all stakeholders.